2020
DOI: 10.3390/educsci10110330
|View full text |Cite
|
Sign up to set email alerts
|

Does Project-Based Learning (PBL) Promote Student Learning? A Performance Evaluation

Abstract: The purpose of the study on which this paper is based was to conduct a performance evaluation of student learning for an introductory course in project management in a higher educational institution in Norway. This was done by utilizing performance measurement philosophy to evaluate perceived student learning after a project-based assignment was applied as an instructional tool. The evaluation was conducted at the end of the semester to determine whether it facilitated learning effectiveness by providing an au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 35 publications
0
39
0
2
Order By: Relevance
“…In that study, there was no analysis of the scores obtained by the students in their exams, but two questionnaires for evaluating the student learning objectives were used to measure the effect of the strategy. The incorporation of a project-based assignment enables the creation of real-life experiences, which further stimulates the creation and development of real-life competencies [42,44]. In our research, we showed that students acquired other learning outcomes and were able to improve their communication skills and applied the scientific method.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In that study, there was no analysis of the scores obtained by the students in their exams, but two questionnaires for evaluating the student learning objectives were used to measure the effect of the strategy. The incorporation of a project-based assignment enables the creation of real-life experiences, which further stimulates the creation and development of real-life competencies [42,44]. In our research, we showed that students acquired other learning outcomes and were able to improve their communication skills and applied the scientific method.…”
Section: Discussionmentioning
confidence: 61%
“…Stratford and Finkel [41] also reported that PBL promoted positive changes in the attitude towards science and the motivation for studying science. PBL has been demonstrated to have a positive impact on student learning, motivation and performance in higher education [42]. This effect can be particularly interesting in highly motivated and demanding students, for whom lecture-based learning could frustrate their expectations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, local waste of CFRP has been increasing recently due to booming growth in using carbon fiber; therefore, part of the commitment toward the society from the university was to increase the awareness through the students by engaging with research projects trying find with solutions to reduce the negative impact. A complete program was designed for the students to be trained on handling the waste in order to proceed with the planned activities, since gaining hands-on skills is an essential matter for the students to acquire knowledge in order to cope with the diverse demands of working life [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…Some research work in the field of serious gaming frameworks exists. In particular, for the use of design patterns [12][13][14], approaches have been based on problem-based learning [15][16][17][18], deep learning [19,20], RETAIN model of FutureLab [21,22], and Evidence-Centered Design [23][24][25]. In this study, we use the Design, Play, and Experience (DPE) framework [26] to study the characteristics of SGs.…”
Section: Study Of Characteristics Of Serious Gamesmentioning
confidence: 99%